Degree of branching in poly(acrylic acid) prepared by controlled and conventional radical polymerization. Issue 19 (15th April 2019) - Maniego, Alison R.; Sutton, Adam T.; Guillaneuf, Yohann; Lefay, Catherine; Destarac, Mathias; Fellows, Christopher M.; Castignolles, Patrice; Gaborieau, Marianne
Abstract : Poly(acrylic acid)s, PAAs and poly(sodium acrylate)s, PNaAs were characterized in detail. Abstract : Poly(acrylic acid)s, PAAs and poly(sodium acrylate)s, PNaAs were characterized in detail. M n was determined using size-exclusion chromatography, 1 H and 13 C NMR spectroscopy. There is no agreement between the results from different methods, possibly due to the surprisingly low solubility of PAA/PNaA in usual solvents such as dioxane, DMSO, and water. Clustering in PAA/PNaA (due to branching) should affect the molar mass determination by SEC and NMR spectroscopy differently. The degree of branching (DB) of PAAs and PNaAs obtained by reversible-deactivation radical polymerization (RDRP) and conventional radical polymerization (CVRP) was quantified by 13 C NMR spectroscopy. Previous investigations indicated that DB in poly( n -butyl acrylate) is lower when synthesized by RDRP than when synthesized by CVRP (without chain transfer agent, CTA). In the present work no substantial differences in DB were observed between PAAs synthesized via RDRP and CVRP in otherwise similar conditions of solvent and temperature. We believe that further investigations are necessary to know whether there are substantial differences in DB between poly( n -butyl acrylate)s synthesized by RDRP and the ones synthesized by CVRP or not. The DB values are higher for PAAs synthesized in dioxane than for PAAs/PNaAs synthesized in water, and adding ethanol to water further lowers the DB values. H-Bonding of ethanol with PAA/PNaA or patching of the mid-chain radical by ethanol can lead to the decrease in DB. The polymerization conditions, polymerization temperature but also solvent, thus allow some tailoring of DB values depending on desired applications. The present manuscript provides an extended, reliable set of experimental data for PAA looking at the influence of polymerization process (controlled versus conventional), temperature, and solvent on DB. This will form a valuable basis for meaningful further in-depth kinetic investigations.